2013
DOI: 10.1097/mao.0b013e318280492b
|View full text |Cite
|
Sign up to set email alerts
|

Workforce Analysis of Neurotologists in the United States

Abstract: The number of specialists in Neurotology likely exceeds projected needs. The current supply of trainees predicts this trend will continue for decades. Development and maintenance of lateral cranial base surgical skills will be difficult for some practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…First, a recent report found that Rochester, Minnesota possessed the second highest ratio of neurotologists per population in the United States. (16) This finding is uniquely relevant to the detection of ILS when existing pathology can be easily overlooked due to its rarity and often subtle radiologic findings. Indeed, in the authors’ experience it is not uncommon that an ILS is identified on secondary review of a scan initially performed elsewhere for sudden or asymmetrical SNHL, after initially being interpreted as normal.…”
Section: Discussionmentioning
confidence: 99%
“…First, a recent report found that Rochester, Minnesota possessed the second highest ratio of neurotologists per population in the United States. (16) This finding is uniquely relevant to the detection of ILS when existing pathology can be easily overlooked due to its rarity and often subtle radiologic findings. Indeed, in the authors’ experience it is not uncommon that an ILS is identified on secondary review of a scan initially performed elsewhere for sudden or asymmetrical SNHL, after initially being interpreted as normal.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the precise need of surgical subspecialists in an ever‐changing medical landscape can be challenging but is important to assess . A 2013 workforce analysis for neurotology determined that, based on predictive population and geographic modeling, the number of neurotologists likely exceeded projected needs and that lateral cranial base practices would be difficult to build and maintain …”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the ratio and regional variation of U.S. neurotologists has suggested a scarcity of neurotologists in certain hospital referral regions. 7 Though the presented results are not meant to reverse‐engineer disease epidemiologies, practical information regarding prescription patterns, drug costs, and potential trending prevalence of medical pathologies can be deduced. Such approach can play a role in better resource and expert allocation by evaluating potentially over‐ or under‐utilized medications, underserved regions, and the prevailing pathologies most commonly presented to neurotologists by Medicare patients.…”
Section: Discussionmentioning
confidence: 99%
“…The cost was standardized by dividing the state's total cost by the number of Part-D eligible residents in that state. Of the states with neurotologists data, this cost ranged between $0.10 and $2.14 per eligible resident neurotologists in certain hospital referral regions 7. Though the presented results are not meant to reverse-engineer disease epidemiologies, practical information regarding prescription patterns, drug costs, and potential trending prevalence of medical pathologies can be deduced.…”
mentioning
confidence: 94%
See 1 more Smart Citation